Кінетичні властивості напівпровідникових кристалів з ізотропними законами дисперсії - Буджак, Я. С. (Видавництво Львівської політехніки, 2013)
Показано, що важливі кінетичні властивості провідних кристалів спричинені умовами дрейфу носіїв зарядів міжвузлями кристалічної ґратки. In this paper it is shown that the important kinetic properties of the conducting crystals are determined by the conditions of the charge carriers drift throw the interstitials of the crystal lattice.
Kinetic properties of semiconductor crystalwith isotropic dispersion law
Keywords: напівпровідниковий кристал; транспортні властивості; кінетичні коефіцієнти; закон дисперсії Кейна; semiconductor crystal; transport properties; kinetic coefficients; Keyn’s dispersion law